2016
DOI: 10.1111/cag.12327
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and resource development impacts in watersheds: Insights from the Nechako River Basin, Canada

Abstract: Few studies to date examine the cumulative effects of climate change and resource development on social‐ecological systems, such as watersheds. In partnership with a watershed alliance we endeavoured to understand the interplay of climate change and resource exploitation impacts in the Nechako River Basin, which drains an area of 52,000 km2 in northwestern Canada as part of the Fraser River Basin. Existing regional climatic studies show a clear warming trend over the last century and a projected mean temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…Frequent forest fires occur in the NRB; the most significant recent events prior to 2015 occurred in 2010 in the Cheslatta Lake area (2916 km 2 burned) and near Cut Off Creek in 2004 (104 km 2 burned). Also, large areas of forest have been cleared for agricultural activity (Nener and Wernick 2000;Picketts et al 2017). As described above, the main anthropogenic impact on water and sediment dynamics within the Nechako River is the Kenney Dam, which was built in the early 1950s, and the subsequent water management policies.…”
Section: Study Area and Sample Collectionmentioning
confidence: 99%
“…Frequent forest fires occur in the NRB; the most significant recent events prior to 2015 occurred in 2010 in the Cheslatta Lake area (2916 km 2 burned) and near Cut Off Creek in 2004 (104 km 2 burned). Also, large areas of forest have been cleared for agricultural activity (Nener and Wernick 2000;Picketts et al 2017). As described above, the main anthropogenic impact on water and sediment dynamics within the Nechako River is the Kenney Dam, which was built in the early 1950s, and the subsequent water management policies.…”
Section: Study Area and Sample Collectionmentioning
confidence: 99%
“…The Canadian Geographer / Le Géographe canadien 2020, 64(3): 475-488 Table 1 Relationships between climate impacts to ecosystems and water supply, and types of resource development in the Nechako Watershed. Summarized from Picketts et al (2017).…”
Section: Background and Contextmentioning
confidence: 99%
“…There are close linkages with the fields of climate change adaptation, resource management, watershed management and cumulative impacts. The purpose of this paper is to further explore these interrelationships, building on past work on climate and resource development in both the Fraser and Nechako Watersheds (e.g., Sanderson et al 2015; Islam et al 2017), including work by Picketts et al (2017), that identified and rated key current intersections between climate change impacts and resource development (Table 1). We attempt to address a range of plausible future possibilities, primarily through the application of scenarios, and reflect on the utility of scenarios, which are broadly used in planning and management, in this context.…”
Section: Introductionmentioning
confidence: 99%
“…The range and scope of possible 'upstream' drivers of change that trigger this cascade are extensive. Climate change can be seen to overlay and compound most drivers of landscape change [43]. Halseth et al note that some natural resource management decisions, such as the allocation of mineral rights or land leases, set in motion a series of pre-determined activities that lead towards a particular type of development debate and trajectory [9].…”
Section: Cumulative Thinking Resource Development and Healthmentioning
confidence: 99%